Chains and chain reactions : study of management control systems in Norwegian IT offshoring to Ukraine - Kurtmollaiev, Seidali (Universitetet i Nordland, 2011)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2011